Moral Values in Selected Folklores of Toraja Tribes - Andi Febriana Tamrin; Yulhaidir Yulhaidir; Wulan Sari Tangnga Lobo' (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This research discusses about the moral values ​​in selected folklore of the Toraja tribe, namely Seredukung and Lakipadada by Junus Bunga Lebang. The purpose of this research is to find out what the moral values are can be found in selected folklores of Toraja tribes. The method used in this research is a qualitative descriptive method. The data is taken from selected Toraja folklore, namely Seredukung and Lakipadada by Junus Bunga Lebang. This research uses Thomas Lickona's conceptual theory of moral values. The results of this research indicates that, there are seven moral values ​​in the selected folklore of the Toraja tribe, namely Seredukung and Lakipadada. There are three moral values that can be found in Seredukung folklore, namely responsibility, tolerance, and self-discipline. While in Lakipadada folklore there are four moral values that can be found namely honesty, helpfulness, cooperation, and courage. Keywords: moral values, folklores of Toraja Tribes, Seredukung, Lakipadada Abstrak Penelitian ini membahas tentang nilai moral pada cerita rakyat terpilih suku Toraja yaitu Seredukung dan Lakipadada karya Junus Bunga Lebang, Tujuan dari penelitian ini adalah untuk mengetahui apa saja nilai-nilai moral yang terdapat dalam cerita rakyat terpilih suku Toraja. Metode yang digunakan pada penelitian ini adalah metode deskriptif kualitif. Data diambil dari cerita rakyat terpilih suku Toraja yaitu Seredukung dan Lakipadada karya Junus Bunga Lebang. Penelitian ini menggunakan teori konsep Thomas Lickona tentang nilai moral. Hasil dari penelitian ini menunjukkan bahwa terdapat tujuh nilai moral pada cerita rakyat terpilih suku Toraja yaitu Seredukung dan Lakipadada. Ada tiga nilai moral yang terdapat dalam cerita rakyat Seredukung, yaitu tanggung jawab, toleransi, dan disiplin diri. Sedangkan dalam cerita rakyat Lakipadada terdapat empat nilai moral yang dapat ditemukan yaitu kejujuran, tolong menolong, kerjasama, dan keberanian. Kata kunci: nilai moral, cerita rakyat suku Toraja, Seredukung, Lakipadada